THE ANALYSIS OF SOCIAL ASSISTANCE INFLUENCE TO EDUCATION PARTICIPATION IN THE PROGRAM FAMILY HOPE POST-EARTHQUAKE - Norman, Moh Nofri; Sakaria, Sakaria; Mengge, Buchari (Universitas Hasanuddin, 2020)
Inequality in inhabitants is one of the negative impacts of uneven development that causes poverty. In 2007, the Indonesian government has been striving to accelerate poverty reduction through the Family Hope Program (PKH) with the Conditional Direct Cash Assistance (BLTB) scheme, known internationally as the Cash Conditional Transfer (CCT). All this time, various studies have assessed that the program has succeeded in encouraging the participation of beneficiary families in achieving welfare in Indonesia. However the facts showed that there is an poverty increase in the city of Mataram after earthquake, even though the family hope program runs normally. Therefore, this research was conducted to see the strength of the social assistance influence on one indicator of welfare, education participation after the earthquake. The survey method was used to obtain information on the distribution of 122 KPM PKH respondents in Bertais village, where the location was severely affected. The results showed that the significance of the influence on cash assistance on the level of education participation was 0.775 or 77.5%. Meanwhile, the significance effect of assistance services on the level of education participation was 0.687 or 68.7%. There is a positive influence on the variable of social assistance (dependent) on educational participation and childcare (independent). Thus it can be concluded that the earthquake did not disturb the PKH cycle so much that it did not become one of the factors causing the increase in poverty in the City of Mataram.